Magnetische Anisotropie und Quantenphasenübergang in CeTi_(1-x)V_(x)Ge_(3) - Kittler, Wolfram (Experimental Condensed Matter Physics / Karlsruher Institut für Technologie, Physikalisches Institut, 2014)
In the present work the substitution series of CeTi_(1-x)V_(x)Ge_(3) is examined. Within the framework of this thesis, several polycrystals and singlecrystals have been made. CeTiGe_(3) is a strong anisotropic ferromagnet with a T_(C) = 14.3 K. When Ti is partially substituted by V, T_(C) is reduced. So CeTi_(1-x)V_(x)Ge_(3) is a potential candidate for a ferromagnetic QCP.